Disaster Preparedness Risk Analysis at Makassar Health Quarantine Center - Chitra Dewi; Ilham Syam; Fahri Umamit; Muhammad Syahrir (Pancasakti Journal Of Public Health Science And Research, 2025)
Fires, as one of the disasters causing significant losses, are often attributed not only to physical or natural conditions but also to human negligence. Therefore, preparedness requires consideration of both physical and social aspects. This study analyzes the risk of disaster preparedness at the Makassar Health Quarantine Center. It employs descriptive research, with a population consisting of all 132 employees at the center. Using purposive sampling, the study included 99 respondents. The findings showed that the emergency response plan was categorized as ready, with 66 respondents (66.7%), followed by the disaster warning system, with 64 respondents (64.6%), and resource mobilization, with 53 respondents (53.5%) in the ready category. The study concludes that, based on disaster preparedness parameters, employees at the Makassar Health Quarantine Center are, on average, very prepared to face disasters. To sustain this level of preparedness, employees are encouraged to remain proactive in activities related to disaster preparedness, ensure access to updated information, and maintain disaster preparedness facilities. Continuous efforts in these areas will help maintain and further improve disaster readiness in the workplace.